Ordered and deterministic cancer genome evolution after p53 loss - Baslan, Timour; Morris, John P.; Zhao, Zhen; Reyes, Jose; Ho, Yu-Jui; Tsanov, Kaloyan M.; Bermeo, Jonathan; Tian, Sha; Zhang, Sean; Askan, Gokce; Yavas, Aslihan; Lecomte, Nicolas; et al. (Nature (London), 2022)
Although p53 inactivation promotes genomic instability 1 and presents a route to malignancy for more than half of all human cancers 2 , 3 , the patterns through which heterogenous TP53 (encoding human p53) mutant genomes emerge and influence tumorigenesis remain poorly understood. Here, in a mouse model of pancreatic ductal adenocarcinoma that reports sporadic p53 loss of heterozygosity before cancer onset, we find that malignant properties enabled by p53 inactivation are acquired through a predictable pattern of genome evolution. Single-cell sequencing and in situ genotyping of cells from the point of p53 inactivation through progression to frank cancer reveal that this deterministic behaviour involves four sequential phases— Trp53 (encoding mouse p53) loss of heterozygosity, accumulation of deletions, genome doubling, and the emergence of gains and amplifications—each associated with specific histological stages across the premalignant and malignant spectrum. Despite rampant heterogeneity, the deletion events that follow p53 inactivation target functionally relevant pathways that can shape genomic evolution and remain fixed as homogenous events in diverse malignant populations. Thus, loss of p53—the ‘guardian of the genome’—is not merely a gateway to genetic chaos but, rather, can enable deterministic patterns of genome evolution that may point to new strategies for the treatment of TP53- mutant tumours. Malignant evolution enabled by p53 inactivation in mice proceeds through an ordered and predictable pattern of Trp53 loss of heterozygosity, accumulation of deletions, genome doubling and the emergence of gains and amplifications.